Principle Analysis and Orientation Mechanism Copy of Chinese Ancient South-pointing Carriage - Chen Wei; Sun Jianjian; Wen Huaixing (Jixie chuandong)
The ancient south- pointing carriage is commonly regarded as the Chinese forerunner of automatic machinery in China,it has a more prominent status in the process of mechanical development. Based on the orientation principle of south- pointing carriage,a new differential gear train orientation mechanism is designed by using seven bevel gears. Furthermore,the model of south- pointing carriage is manufactured according to this structure design. The physical mode and relevant test confirmed the orientation function of this mechanism,and it is pointed that the transmission structure of this mechanism is simple and reliable. So the orientation mechanism can provide some technical reference for the selection of orientation system.